Influence Of It Affordance On Purchase Intention On Shopee Live Feature In Surabaya City - Hannah Emmanuella Delia; Sonja Andarini (UNIVED Press, 2024)
Purchase Intention on the shopee live feature. The population used is residents of Surabaya City with criteria determined before the study, therefore the sampling technique uses purposive sampling so that a sample of 100 respondents is obtained. Data analysis techniques use validity tests, reliability tests, classical assumption tests consisting of normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests, multiple linear regression analysis, hypothesis tests (F test and t test), which are processed with SPSS 27. The calculation results of the F test show a calculated F value of 44.613 and a table F value of 2.689 with a signification value of 0.001 > 0.05, then the variables Visibility Affordance, Metavoicing Affordance, and Guidance Shopping Affordance simultaneously affect Purchase Intention. The result of the multiple linear regression calculation is Y = -0.746 + 0.107 X1 + 0.274 X2 + 0.577 X3 + e. Based on the results of this study proves that visibility affordance has no partial effect on purchase intention, metavoicing affordance has partial effect on purchase intention, guidance shopping affordance has partial effect on purchase intention.